Detection of the primary lesion in patients with cervical metastases from unknown primary tumors with narrow band imaging endoscopy: Preliminary report. Issue 1 (8th April 2012) - Ryu, In Sun; Choi, Seung‐Ho; Kim, Do Hun; Han, Myung Woul; Roh, Jong‐Lyel; Kim, Sang Yoon; Nam, Soon Yuhl
Abstract: Background: We investigated whether the addition of narrow band imaging (NBI) to standard diagnostic workups could enhance the detection of primary lesions in patients with carcinoma of unknown primary (CUP). Methods: Thirty patients with CUP underwent NBI endoscopy and fluorodeoxyglucose–positron emission tomography/CT (FDG‐PET/CT) after thorough conventional diagnostic workups between 2009 and 2011. Sites suspected of harboring primary tumors, as determined by NBI and/or FDG‐PET/CT, were biopsied for histologic confirmation. Results: Occult primary tumors were identified in 33.3% (10/30), including 13.3% (4/30) by NBI and 20.0% (6/30) by FDG‐PET/CT. All of diagnosed lesions by NBI were confirmed histologically as squamous cell carcinomas with T1 classification and identified at 2 supraglottis, 1 hypopharynx, and 1 esophagus, respectively. Conclusions: NBI endoscopy may be a useful method for detecting primary tumors, especially for small and superficial squamous cell carcinomas of the upper aerodigestive tract, after conventional workup in patients with CUP. © 2012 Wiley Periodicals, Inc. Head Neck, 2013